1995
DOI: 10.1063/1.114492
|View full text |Cite
|
Sign up to set email alerts
|

Carbonization-induced SiC micropipe formation in crystalline Si

Abstract: The defect structure of Si substrates at their β-SiC/Si interfaces generated in a chemical vapor deposition (CVD) process by carbonization with C2H4 has been investigated in detail by transmission electron microscopy (TEM) using differently prepared cross section and planar specimens. A new category of defects of minute size and high area density has been found and identified as SiC micropipes formed by Si outdiffusion and simultaneous ingrowth of SiC. A model of self-adjusting micropipe formation is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In fact, surface diffusion is an important mass transport mechanism in powder sintering of metals and ceramics, which gives rise to coarsening and enhancement of pore growth. Furthermore, it has been recognized that surface diffusion can be the main mechanism accounting for the elongation of carbon nanotubes, , and inorganic nanowire/tubes, , when the characteristic diffusion length ( D s τ s ) 1/2 > l (length of a nanowire or tube). In the study of carbonization of a crystalline Si substrate, Scholz et al observed micropipes extending inward from the Si surface. According to the authors, a self-adjusting process was involved in which Si out-diffuses over the wall of the pipes to the wafer surface, where Si finally reacts to form SiC.…”
mentioning
confidence: 99%
“…In fact, surface diffusion is an important mass transport mechanism in powder sintering of metals and ceramics, which gives rise to coarsening and enhancement of pore growth. Furthermore, it has been recognized that surface diffusion can be the main mechanism accounting for the elongation of carbon nanotubes, , and inorganic nanowire/tubes, , when the characteristic diffusion length ( D s τ s ) 1/2 > l (length of a nanowire or tube). In the study of carbonization of a crystalline Si substrate, Scholz et al observed micropipes extending inward from the Si surface. According to the authors, a self-adjusting process was involved in which Si out-diffuses over the wall of the pipes to the wafer surface, where Si finally reacts to form SiC.…”
mentioning
confidence: 99%
“…TEM images (Fig. 2) show a good SiC/Si interface, free of micropipes or voids in the Si substrate, usually characterizing these heterostructures [5,6]. The spots of the Selected Area Diffraction (SAD) pattern (Figure 2b) show that the layer is monocrystalline and (001) oriented.…”
Section: Resultsmentioning
confidence: 95%
“…Some of the carbon atoms form Si-C bonds by Si outdiffusion at the Si/C interface. 19 Through diffusion, microindentions, i.e., voids, are created at the top of a silicon substrate. 15 Then the optically equivalent thickness for the first 2 min is due to a surface layer mainly including weakly bonded carbon like sp 2 one, sp 3 carbon, silicon, voids, and Si-C.…”
Section: Department Of Electronics and Information Science Kyoto Insmentioning
confidence: 99%